If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = k + 15 Reorder the terms: 9 = 15 + k Solving 9 = 15 + k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1k' to each side of the equation. 9 + -1k = 15 + k + -1k Combine like terms: k + -1k = 0 9 + -1k = 15 + 0 9 + -1k = 15 Add '-9' to each side of the equation. 9 + -9 + -1k = 15 + -9 Combine like terms: 9 + -9 = 0 0 + -1k = 15 + -9 -1k = 15 + -9 Combine like terms: 15 + -9 = 6 -1k = 6 Divide each side by '-1'. k = -6 Simplifying k = -6
| 7(6p+6)=8p-26 | | 7(6x+4)=4x-10 | | 5x^2+3x+2=0 | | 30-8m=7m-6(3m-3) | | 8+8p=3(4p-8) | | 5k-33=6(5k+7) | | 8(1+4x)-7x=8+4x | | 2(5x+1)+2=3(x-1) | | x+z=c*d | | d-4=-24 | | 9x^2-64= | | 4(2b+3)=b+12 | | 4x-8=x+12 | | y=-4(24)-4 | | y=-4x-4 | | 320v^2-245=0 | | x+2x=1049 | | .8a-6=.6a+22 | | -14(45)+3x=29 | | d-7=-17 | | 320v^2-361=0 | | 320v-361=0 | | 12-35x=45 | | (5x-4)(6x+4)=0 | | -3(4s-3)-9=-2(8s+8)-3 | | -5t^2+6t+10=0 | | x^2+2x^2-20=0 | | -25=-3-(-y) | | (x-4)(3x+4)=0 | | 6-6(-4v+2)=-6+8v | | .42x=1 | | 2x^3-2x^2-8x+4=0 |